Analisis Sumur Resapan Sebagai Pengendali Genangan Pada Perumahan Sompu Raya, Kelurahan Kallabirang, Kabupaten Takalar - Romdhani, Sulthon Kharomaeni; Yusuf, Andi Rumpang; Badrun, Burhanuddin (Program Studi Teknik Sipil Universitas Bosowa, 2024)
The importance of housing control in housing cannot be ignored. Inundation in housing can cause various problems such as infrastructure damage, poor environmental sanitation, and health problems. Therefore, inundation control is very important. One method that can be used to control deposition is to use infiltration wells. Infiltration wells are an effective way to overcome the problem of stagnant water in the train area. The aim of this study was to analyze infiltration wells as structural controllers at Sompu Raya Housing, Kallabirang Village, Takalar Regency. This research was conducted using a field survey and literature study method. The data obtained were analyzed using qualitative and quantitative methods. The results of this study indicate that 189 units of infiltration wells are needed to overcome inundation with 100% efficiency of air seeping into the ground with a duration of 1 hour, while the efficiency of infiltration wells by applying it to each house is 83.95%.